Analysis of the Effect of Motivation, Organizational Culture, and Compensation on the Performance of Generation Z and Millennial Employees at PT. Media Edutama Indonesia - Iswadi, Melani Tissa; Subarjo, Subarjo (Dinasti Publisher, 2025)
This study aims to examine the influence of motivation, organizational culture, and compensation on the performance of Generation Z and Millennial employees at PT Media Edutama Indonesia. Using quantitative methods with questionnaires as the main instrument, this study involved 50 employee respondents. The results of the analysis show that organizational culture and compensation have a significant positive effect on employee performance, while motivation does not show a significant effect. The findings indicate that to improve employee performance, companies need to focus on developing a positive organizational culture and a fair compensation system. The results of this study contribute to a better understanding of the factors that influence the performance of younger generation employees, as well as practical implications for companies in designing effective human resource management strategies.